Recent advances in analytical figures of merit: Heteroscedasticity strikes back - Allegrini, Franco (2017)
With a growing number of analytical methodologies incorporating multivariate calibration models, the development of suitable estimators of their analytical figures of merit is playing an important role in modern analytical chemistry. The main goal of this mini-review is to briefly present the recent trends regarding reliable and interpretable estimators of traditional figures of merit such as sensitivity, prediction uncertainty and detection limit. Heteroscedasticity in instrumental measurements is driving some of these recent developments and influencing the definition of new estimators.